Student experiences of computer assisted instruction: a case study - Donnelly, Richard B., author; Timpson, William, advisor; Quick, Don, advisor; Banning, James H., committee member; Smith, Kenneth, committee member (Colorado State University. Libraries, 2002)
An evaluation of the acceptance of this delivery system by the students will benefit the academic community in its endeavor to prepare and deliver courses with the use of technology. The information gathered from this study will benefit the instructor, who is challenged to plan ahead, prepare beyond the immediate future and be available to the student, whose satisfaction with learning is imperative. Participant responses focused on the student experiences of Computer Assisted Instruction (CAI) are discussed and both the positive and the negative aspects of CAI are presented. Recent literature has noted the variety of methods to teach distance education courses with the use of technology. Technology is causing tremendous changes in the way people communicate with each other and how they gain access to various types of information. All these changes are important for faculty to understand both in terms of how technology applies to particular disciplines and how courses can be taught. This information is intended to provide educators insight into technology, including applications that can affect their educational efforts. Computer Assisted Instruction (CAI), teaching and learning inherently give pedagogical and technology challenges to teachers, students, and administrators. Three themes, in particular, emerged from the course under investigation—Course Design Flexibility, Instructor Interaction, and the Variety of Technology Tools. Some participants in this study reported that the flexibility of the Computer Assisted Instruction (CAI) enabled them to Iearn during periods of them daily/weekly schedule when they were fresh, and thereby, better prepared to make instructional gains. Findings of the present case study indicate that the time and convenience dimension of course flexibility to be of substantial benefit, especially students engaged in professional employment and/or parenting. Some students in this research were distressed that the orientation session offered by the instructor during the first week of class was not adequate. The results strongly suggest that participants relied heavily upon the instructor's familiarity with computer-based technologies. Some students in this research study continued to have problems with the technological dimension of the course. Typically, they relied upon the course instructor for assistance in these cases. Based upon the data received from the students in this case study, the researcher has concluded that instructors utilizing CAI must be prepared to perform dual roles as experts in their field and as teachers of computer usage.
Keywords: educational technology